2017
DOI: 10.4306/pi.2017.14.6.762
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Suicidal Ideation and Related Factors among North Korean Refugees in South Korea

Abstract: ObjectiveAccording to previous social survey, a high number of North Korean refugees (NKRs) in South Korea had suicidal ideation. The purpose of this study is to examine the related factors for suicidal ideation among NKRs by gender in South Korea.MethodsWe examined the sample of NKRs, 701 subjects (men=160, women=-541) residing in South Korea, the participants were enrolled from October 2008 to May 2014. The related factors with suicidal ideation in NKRs were analyzed via a logistic regression analysis.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Females usually seek social support more than males, and lacking of it during or after displacement times being the most coherent prognosticator of negative consequences of traumas [ 23 ]. The higher scores of depression thoughts and anxiety symptoms among females in our study was supported by many other studies [ 13 , 16 , 50 , 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Females usually seek social support more than males, and lacking of it during or after displacement times being the most coherent prognosticator of negative consequences of traumas [ 23 ]. The higher scores of depression thoughts and anxiety symptoms among females in our study was supported by many other studies [ 13 , 16 , 50 , 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Considering the considerable stigma surrounding mental illness and the low health literacy of NKDs residing in South Korea, it is necessary to provide community-based information to vulnerable groups to promote knowledge of mental illness and ensure the safe use of medications. [20,22,37] • Repatriation experiences [38] • Long staying periods after entrance [21,22,44] • Perceived discrimination [10] • Low income [13,46,47] • Family relationships (family violence, family cohesion) [17,48,49] • Physical illnesses [19,51] • Alexithymia [31] • Emotion regulation strategy [40] • Thoughts of personal failure [41] • Resilience [42]…”
Section: Discussionmentioning
confidence: 99%
“…A 7-year follow-up study on the mental health of NKDs in South Korea reported that the rate of PTSD and PTSD symptom scale scores decreased significantly from baseline over the study period [43]. However, staying more than 5 years after entering South Korea was related to high rates of suicidal ideation among NKDs [22,44]. Additionally, female adult NKDs who had been resettled in South Korea for longer periods experienced more severe depressive symptoms than those in the earlier stages of resettlement [21].…”
Section: Psychosocial Stress During Adaption To New Society and Its Rmentioning
confidence: 99%
“…Empirical studies on refugees or immigrants have consistently suggested that females generally show higher suicide risks both in ideation and attempts, compared to residents of the host country (Burger et al, 2009; Burvill, 1998; Kosidou et al, 2012; Ratkowska & Leo, 2013; Yilmaz & Riecher‐Rössler, 2012). Previous studies on suicidality of NKRW have found that major factors associated with suicidal risk include depression (Im et al, 2017; An et al, 2018; Um et al, 2015), social isolation (Ryu & Park, 2018), alcohol misuse (Kim et al, 2017), and life stress (Kim et al, 2013; Noh et al, 2017). However, previous studies on NKRW’s suicidal risk did not differentiate suicide attempt from suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Life experiences and stress in the course of their adjustment in South Korea put NKRW in great danger of suicidal behaviors (Noh et al, 2017). Empirical studies on refugees or immigrants have consistently suggested that females generally show higher suicide risks both in ideation and attempts, compared to residents of the host country (Burger et al, 2009; Burvill, 1998; Kosidou et al, 2012; Ratkowska & Leo, 2013; Yilmaz & Riecher‐Rössler, 2012).…”
Section: Introductionmentioning
confidence: 99%